1978
DOI: 10.2307/3279618
|View full text |Cite
|
Sign up to set email alerts
|

Cuticular Morphology of Five Species of Dirofilaria: A Scanning Electron Microscope Study

Abstract: Cuticular markings of five species of Dirofilaria were examined by SEM. Variations in the patterns on the en face view were observed among the species. Transverse striations were observed on the cuticles of all five species, but longitudinal ridges were lacking on Dirofilaria immitis, the type species of the subgenus Dirofilaria. They were present on the other four species, Dirofilaria repens, Dirofilaria tenuis, Dirofilaria corynodes, and Dirofilaria magnilarvatum, members of the subgenus Nochtiella. Longitud… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
19
0

Year Published

1981
1981
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(23 citation statements)
references
References 8 publications
4
19
0
Order By: Relevance
“…In contrast, terminal post-cloacal papillae were best seen by SEM. The pre-cloacal papillae distribution is similar to the descriptions of Wong and Brummer (1978) and Rodrigues-Silva et al (1999), although Ló pez-Neyra (1947) described a different distribution of post-cloacal papillae for D. immitis. Based on this variability, Rodrigues-Silva et al (1999) concluded that the cloacal papillae distribution cannot be considered as a reliable taxonomic character for D. immitis.…”
Section: Remarkssupporting
confidence: 69%
See 3 more Smart Citations
“…In contrast, terminal post-cloacal papillae were best seen by SEM. The pre-cloacal papillae distribution is similar to the descriptions of Wong and Brummer (1978) and Rodrigues-Silva et al (1999), although Ló pez-Neyra (1947) described a different distribution of post-cloacal papillae for D. immitis. Based on this variability, Rodrigues-Silva et al (1999) concluded that the cloacal papillae distribution cannot be considered as a reliable taxonomic character for D. immitis.…”
Section: Remarkssupporting
confidence: 69%
“…Unpaired pre-cloacal (4-5); 3-5 pairs postcloacal (first and fourth laterally dislocated papillae) + frequently an unpaired papillae + unique terminal papillae Brummer (1978), who described D. immitis without longitudinal cuticular ridges using SEM. Because of these discrepancies, we carried out a detailed morphological study in D. immitis using light microscopy and SEM.…”
Section: Remarksmentioning
confidence: 99%
See 2 more Smart Citations
“…Based upon these morphological characteristics the worm was identified as an immature, male Dirofilaria immitis, the canine heartworm. [4][5][6] Polymerase chain reaction confirmation. Using the out- line of the positive histological section as a guide, the preserved, unsectioned portion of the spermatic cord that had harbored the positive sections was identified, and an examination of the wet tissue under a dissecting microscope permitted identification of the infected artery.…”
Section: Case Reportmentioning
confidence: 99%